The Family Function and Exercise Behavior of Chinese College Students: A Moderated Mediation Model of Exercise Value Cognition and Only-Child Status - Wu, Ming; Wu, Pei-Yao; Yang, Jian; Li, Xin (Frontiers in Psychology, 2021)
The purpose of this study is to investigate the mediating role of exercise value cognition between family function (FF) and exercise behavior and the moderating role of an only-child status. A questionnaire survey was conducted on 504 Chinese college students using the FF scale, the exercise value cognition scale, and the exercise behavior scale. The analysis yielded four main findings. (1) There are significant differences between an only-child and a non-only-child for negative exercise behavior and FF. The only-child group has a higher average FF score and a lower average negative exercise score. (2) Exercise behavior and four of its dimensions—exercise autonomy, attention control, exercise planning, and situational induction—are each significantly positively correlated with FF and exercise value cognition. (3) FF is a significantly positive predictor of exercise behavior, both directly and through exercise value cognition, which plays a partial mediating role. (4) Only-child status significantly moderates the mediating effect of exercise value cognition in the link between FF and exercise behavior. The intergroup differences mainly manifest in the influence of FF on exercise behavior and the influence of exercise value cognition on exercise behavior. In the only-child subsample, exercise value cognition plays a complete mediating role. The results of the current study demonstrated the important role that FF and exercise value cognition played in promoting the exercise behavior of college students. These findings have important implications for exercise behavior in adolescents by maintaining sound communication between family members and developing a healthy lifestyle or value cognition.